Changes from 2012 to 2015 in intravenous fluid solutions issued to hospital departments. Issue 5 (May 2017) - Jonsson, A. B.; Perner, A.
Abstract : Background: In recent years, large trials have increased the level of evidence for intravenous (IV) fluid therapy, at least in the intensive care setting. It is less clear whether this change in the evidence base has been associated with changes in IV fluid use in different hospital departments. Methods: We obtained details from the regional pharmacy regarding IV fluids issued to hospital departments in the Danish Capitol Region from January 2012 to May 2015. We used paired Wilcoxon's signed‐rank test to analyse changes in the issuing in different departments. Results: Total regional issuing of IV fluids showed increase in crystalloid solutions (9%; P  = 0.001) and decrease in colloid solutions (59%; P  = 0.005). Subtype analysis showed increased issuing of buffered crystalloids (36%; P  = 0.001), human albumin (30%; P  < 0.0001) and decreased issuing in synthetic colloid solutions (82%; P  < 0.0001) from Q1 2012 to Q2 2015. At the departmental level, the issuing of synthetic colloid solutions decreased markedly to all settings. The issuing of buffered crystalloids increased to orthopaedic (226%; P  = 0.03) and to general surgery departments (686%; P  = 0.002). Albumin solutions were increasingly issued to anaesthesia departments (63%; P  = 0.005) and was rarely issued to general surgery and orthopaedic departments. Conclusions: The issuing of IV fluid solutions to hospital departments has changed markedly over the last years to less colloid, in particular the synthetic solutions, and relatively more issuing of crystalloids, in particular the buffered solutions.